The Effects of Different Cytokinin Types and Their Concentration on in Vitro Growth of Apricot (Prunus armeniaca L.) Shoots - Šiško, Metka; Ternjak, Tina; Grobelnik-Mlakar, Silva (Agricultura Scientia, 2022)
The objective of this study was to assess the effects of different cytokinin types [(6-benzylaminopurine (BAP), thidiazuron (TDZ) and meta-topolin (mT)] and their concentration on in vitro growth of apricot shoots. Sufficiently developed shoots were transferred to different multiplication media, which differed regarding the presence of cytokinin and its concentration. The subcultivation period lasted nine weeks. Analysis of covariance (ANCOVA) was performed to investigate the influence of plant growth regulators and their concentration on the final shoot weight of obtained tissue per regenerating explant. The results showed that all three cytokinins had a positive effect on shoot growth. There was a significant difference between used concentrations in the case of TDZ and BAP, while in the case of mT, the concentration did not significantly affect shoots’ regeneration. In our study, the most significant increase in shoots weight was obtained on medium supplemented with 1.0 mg/L BAP.
Keywords: Prunus armeniaca; micropropagation; in vitro propagation; BAP; TDZ; mT